Modifikasi Algoritma Kriptografi Hill Chiper dengan Matriks Generalisasi Bilanga Fibonacci dalam Penyandian Pesan - Husni Fitroti; Mamika Ujianita Romdhini; Ni Wayan Switrayni (University of Mataram, 2021)
Hill Cipher algorithm is a technique of message encoding by implementing a matrix of order as a key matrix. The key matrix is a matrix that has a multiplicative inverse. The security of message is measured by the number of processes in encoding. The more processes in encoding the longer time it takes. Consequently, the massage will be more secure. The purpose of this research is to modify the Hill Cipher algorithm by using generalized Fibonacci matrix whose degree-p and rank-n . This research showed that for any non-negative integer p and positive integer n, matrix can be used as a key matrix in Hill Cipher algorithm. The modification of the Hill Cipher algorithm has been done by modifying the former key by making the degree and rank of as the key used in the encryption and decryption process of data (message).